Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3892/ijmm.2012.1164
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelium, age-related macular degeneration and neurotrophic keratouveitis

Abstract: Abstract. Age-related macular degeneration (AMD) is the leading cause of impaired vision and blindness in the aging population. The aims of our studies were to identify qualitative and quantitative alterations in mitochondria in human retinal pigment epithelium (RPE) from AMD patients and controls and to test the protective effects of pigment epithelium-derived factor (PEDF), a known neurotrophic and antiangiogenic substance, against neurotrophic keratouveitis. Histopathological alterations were studied by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…In the murine RPE, metabolic or oxidative stress resulted in the formation of large mitochondria produced by activation of the P13/AKT/mTor signaling pathway 47 . From our data, a decrease in mitochondrial size with age appears to be the normal progression in WT zebrafish, which has also been observed in human RPE cells 48,49 . To explore whether the abnormal growth in the obe td15 retina may be related to alterations in the mitochondrial dynamics, we investigated fis1 and opa1 expression as indicators of fission and fusion, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…In the murine RPE, metabolic or oxidative stress resulted in the formation of large mitochondria produced by activation of the P13/AKT/mTor signaling pathway 47 . From our data, a decrease in mitochondrial size with age appears to be the normal progression in WT zebrafish, which has also been observed in human RPE cells 48,49 . To explore whether the abnormal growth in the obe td15 retina may be related to alterations in the mitochondrial dynamics, we investigated fis1 and opa1 expression as indicators of fission and fusion, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Quantitative analysis confirmed the significantly increased presence of autophagic structures in PD cells (Figure 6G ; p < 0.01, Unpaired t- test). Furthermore, in addition to typical autophagosomes and autophagolysosomes (Figures 6C,F ; black arrows, black arrowhead showing high magnification of an autophagolysosome) a marked increase in very dense structures, potentially compatible with lysosomes containing undegraded residues, was seen broadly in PD cells (Figures 6D,E,I ; white arrows; Bianchi et al, 2013 ; Biswal et al, 2016 ). Given the autofluorescent nature of lipofuscin, flow cytometry was used to analyze autofluorescence levels in the fibroblasts.…”
Section: Resultsmentioning
confidence: 86%
“…In addition to glycolysis, mitochondrial function is also essential for proper photoreceptor function, as deletion of the mitochondrial pyruvate carrier (MPC1) in the neuroretina results in retinal degeneration 42 . Several findings have also implicated metabolic dysregulation in the pathogenesis of AMD 4345 . In this disease, RPE dysfunction is considered a primary event, and studies have shown that RPE stability and its ability to support retinal function is reduced when it is forced to rely on glycolysis 46 .…”
Section: Discussionmentioning
confidence: 99%